Are Islamic Banks Affected By Conventional Bank Interest Rates? The Case of Tukiye - Hasan KAZAK (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
The purpose of this study is to reveal the empirical causal relationship between the variables that affect the profit rates distributed to deposits at participation banks. In this study, monthly data for the period 2002:M01-2022:M02 were used in order to reveal the variables affecting the profit share rates distributed to deposits by participation banks. In order to analyze the relationship between the variables, the Johansen cointegration test, impulse-response analysis were used within the framework of the VAR model, and the effect ratios of the variables were revealed with the var decomposition table. In addition, the causality relationship was discussed with the Toda-Yamamoto causality test. In the study, a model has been developed that reveals the variables that affect the change in the profit share rate of participation banks distributed to time deposits. In the analyzes made, it has been revealed that the interest rates of conventional banks are effective on the profit share rates of participation banks in accordance with the literature in the case of Turkiye. VAR Decomposition results; It shows that approximately 38.05% of the change in the profit share ratio of participation banks distributed to time deposits in the 10th period is explained by the interest rate given to 1-year maturity deposits of conventional banks operating in Turkiye.